The problem of social security of residents of rural areas of Russia in modern conditions: social and philosophical dimension - Shilovtsev Andrey; Sorokina Natalia; Stozhko Konstantin; Lopez Garcia Jose Luis (E3S Web of Conferences, 2020)
The article considers the problem of social security of rural residents from a socio-philosophical point of view in the context of the need to further strengthen it and improve the entire system of social and labor relations. The morphology of social security and its features in the conditions of modern agricultural production are revealed. Identified shortcomings of existing calculation of the minimum wage (SCMW) and the minimum subsistence level (MSL) as a factor in their failure to comply with the required level of social security of the rural population. The main causes and forms of devaluation of social security in rural areas (underdevelopment of industrial and social infrastructure, migration of rural population to megacities, etc.) are identified. Measures are proposed to strengthen the social security of the rural population, taking into account all its components.